Computer Access Evaluations for Persons with Disabilities. - Heinisch, Barbara (1995)
Keywords: dept.sed; faculty_collection; sabbatical_report

The Role of Constructivism in the Mathematics Education of Learning Disabled Students. - Johnston, Elizabeth (1994)
Keywords: dept.sed; faculty_collection; sabbatical_report

Roads to Reading Disability: When Poor Readers Become "Learning Disabled" - Spear-Swerling, Louise (1993)
Keywords: dept.sed; faculty_collection; sabbatical_report

Case Studies on Teaching Special Needs and at-Risk Students. - Piazza, Robert (1992)
Keywords: dept.sed; faculty_collection; sabbatical_report

A Study of Methods of Integrating Whole Language Instruction and Direct Instructional Procedures. - Taylor, Maravene (1991)
Keywords: dept.sed; faculty_collection; sabbatical_report

Educating and Training the Mentally Retarded in Israel. - Levy, Irwin (Spring ; Special Education., 1990)
Keywords: dept.sed; faculty_collection; sabbatical_report

Perspectives on Learning Disabilities: Biological, Cognitive, Contextual - Sternberg, Robert J.; Spear-Swerling, Louise (Westview Press, 1999)
Keywords: Education; Learning disabilities; Learning disabilities; Learning disabled children; Physiological aspects; Constructivism (Education); Context effects (Psychology) in children; award_winner; dept.sed; faculty_collection

Teaching for Thinking - Sternberg, Robert J.; Spear-Swerling, Louise (Psychology in the classroom, 1996)
Keywords: Study and teaching; Thought and thinking; United States; United States; Creative thinking; dept.sed; faculty_collection

The Parent Teacher Partnership - Barsch, Ray H. (Council for Exceptional Children, 1969)
Keywords: Children with disabilities; Education; Parent-teacher relationships; dept.sed; faculty_collection

The Physical, Personality, and Academic Status of Children Who Are Mentally Retarded Attending Special Classes as Compared with Children Who Are Mentally Retarded Attending Regular Classes - Blatt, Burton (1958)
Keywords: Children with mental disabilities; Education; dept.sed; faculty_collection

An interpersonal skills workshop for preparing special education teachers - Gerber, S.A.; Drezek, S. (Education and the Training of the Mentally Retarded, 1977)
The findings in this study that self reported acceptance of self and others and interpersonal skills increased following the Workshop must themselves be regarded within the limitations of a small sample, an analysis of only one leader's group participants, measurements by ratings, and a quasi experimental design. Nevertheless, human relations training appears to be a valuable component to program more systematically into teacher education. Work in developing specific training goals and procedures relevant to personal growth as related to competence in the classroom is the next step. The fact that such a short training program could affect the way student teachers feel about themselves should encourage further research and experimentation.
Keywords: dept.sed; mental deficiency; methodology; normal human; psychodrama; teacher; theoretical study; training; vocational education; ⛔ No DOI found

The road not taken: an integrative theoretical model of reading disability. - Spear-Swerling, L.; Sternberg, R.J. (Journal of learning disabilities, 1994)
This article describes a theoretical model of reading disability that integrates a wide range of research findings in cognitive psychology, reading, and education across the age and grade span. The model shows how reading disability relates to normal reading acquisition, and includes four possible patterns of reading disability: nonalphabetic readers, compensatory readers, nonautomatic readers, and readers delayed in the acquisition of word-recognition skills. We compare our model to the models of other investigators and argue that our model is especially useful to practitioners. Finally, we discuss some of the educational implications of the model.
Keywords: Adolescent; Adult; Child; Dyslexia; Education, Special; Educational Status; Humans; MLCS; MLOWN; Mental Recall; Phonetics; Verbal Learning; adolescent; adult; child; dept.sed; dyslexia; education; educational status; human; learning; phonetics; psychological aspect; recall; review

Teaching test taking skills - Rothman, Rosalind W; Cohen, Jill (Intervention In School And Clinic, 1988)
Many special education students have the knowledge but are unable or unprepared to demonstrate that knowledge while taking a test. © 1988, SAGE Publications. All rights reserved.
Keywords: dept.sed

Cognitive assessment with disabled readers - Spear, Louise C.; Sternberg, Robert J. (Special services in the schools, 1986)
This paper describes an approach to cognitive assessment that involves a synthesis of the traditional psychometric approach and the more recent information-processing approaches. In this combined approach, psychometric tests arc supplemented by tasks adapted from information-processing research. The paper focuses on the use of the approach with disabled readers, although the approach may be generalized to many different populations. The Test of Syllable and Phoneme Counting, a measure of awareness of the sound structure of speech, is described, as an example of an information-processing task that would be useful with younger disabled readers. Guidelines for using information-processing measures are also discussed. © 1986 by The Haworth Press, Inc. All rights reserved.
Keywords: dept.sed

Research implications on choosing a program to teach about disabilities - Heinisch, BS (Rehabilitation Literature, 1981)
Keywords: Attitude to Health; Disabled Persons; Human; Individuality; Prejudice; Stereotyping; Teaching; attitude; dept.sed; disabled; education; musculoskeletal system; normal human; psychological aspect; school child; therapy; ⛔ No DOI found

Learning from Living: Dear Rachel - Kronick, Doreen; Rothman, Rosalind (Academic Therapy, 1980)
Keywords: dept.sed

Test accommodations for students with disabilities - Spear-Swerling, L (Contemporary Psychology-Apa Review of Books, 1999)
Keywords: dept.sed

Social perceptions of people with disabilities in history - Spear-Swerling, L (Contemporary Psychology, 1999)
Keywords: dept.sed

Curing our `epidemic' of learning disabilities - Spear-Swerling, L; Sternberg, RJ (Phi Delta Kappan, 1998)
Keywords: dept.sed; ⛔ No DOI found

Off Track: When Poor Readers Become "Learning Disabled" - Spear-Swerling, Louise; Sternberg, Robert J. (Renewing American schools, 1996)
Autorías: Louise Spear-Swerling, Robert J. Sternberg. Año de publicación: 1996. Libro en Dialnet.
Keywords: Reading disability; United States; United States; Learning disabilities; dept.sed; faculty_collection

The ethics of special-education - howe,kr, miramontes,ob - Levy, IS (American Journal on Mental Retardation, 1994)
Keywords: dept.sed; ⛔ No DOI found

The Study and Teaching of Ethics for Persons with Mental-Retardation - Dykeman, KJ; Levy, IS (Mental Retardation, 1991)
Keywords: dept.sed; ⛔ No DOI found